Measurement of the t(t)over-bar production cross-section using e mu events with b-tagged jets in pp collisions at root s=7 and 8 TeV with the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Khalek, SA; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; Abreu, H; Abreu, R; et al. (Springer New York LLC, 2014)
The inclusive top quark pair (Formula presented.) pair in the final state. The measurement was performed with the 2011 7 TeV dataset corresponding to an integrated luminosity of 4.6 (Formula presented.)-tag a jet from a top quark decay, thereby minimising the associated systematic uncertainties. The cross-section was measured to be: (Formula presented.)where the four uncertainties arise from data statistics, experimental and theoretical systematic effects, knowledge of the integrated luminosity and of the LHC beam energy. The results are consistent with recent theoretical QCD calculations at next-to-next-to-leading order. Fiducial measurements corresponding to the experimental acceptance of the leptons are also reported, together with the ratio of cross-sections measured at the two centre-of-mass energies. The inclusive cross-section results were used to determine the top quark pole mass via the dependence of the theoretically predicted cross-section on (Formula presented.) GeV. By looking for an excess of (Formula presented.) production with respect to the QCD prediction, the results were also used to place limits on the pair-production of supersymmetric top squarks (Formula presented.) with masses close to the top quark mass, decaying via (Formula presented.) to predominantly right-handed top quarks and a light neutralino (Formula presented.), the lightest supersymmetric particle. Top squarks with masses between the top quark mass and 177 GeV are excluded at the 95 % confidence level.